Pyruvate dehydrogenase kinase 4 promotes ubiquitin–proteasome system‐dependent muscle atrophy. Issue 6 (19th October 2022) - Sinam, Ibotombi Singh; Chanda, Dipanjan; Thoudam, Themis; Kim, Min‐Ji; Kim, Byung‐Gyu; Kang, Hyeon‐Ji; Lee, Jung Yi; Baek, Seung‐Hoon; Kim, Shin‐Yoon; Shim, Bum Jin; Ryu, Dongryeol; Jeon, Jae‐Han; et al.
Abstract: Background: Muscle atrophy, leading to muscular dysfunction and weakness, is an adverse outcome of sustained period of glucocorticoids usage. However, the molecular mechanism underlying this detrimental condition is currently unclear. Pyruvate dehydrogenase kinase 4 (PDK4), a central regulator of cellular energy metabolism, is highly expressed in skeletal muscle and has been implicated in the pathogenesis of several diseases. The current study was designed to investigated and delineate the role of PDK4 in the context of muscle atrophy, which could be identified as a potential therapeutic avenue to protect against dexamethasone‐induced muscle wasting. Methods: The dexamethasone‐induced muscle atrophy in C2C12 myotubes was evaluated at the molecular level by expression of key genes and proteins involved in myogenesis, using immunoblotting and qPCR analyses. Muscle dysfunction was studied in vivo in wild‐type and PDK4 knockout mice treated with dexamethasone (25 mg/kg body weight, i.p., 10 days). Body weight, grip strength, muscle weight and muscle histology were assessed. The expression of myogenesis markers were analysed using qPCR, immunoblotting and immunoprecipitation. The study was extended to in vitro human skeletal muscle atrophy analysis. Results: Knockdown of PDK4 was found to prevent glucocorticoid‐induced muscle atrophy and dysfunction in C2C12 myotubes, which was indicated by induction of myogenin (0.3271 ± 0.102 vs 2.163 ± 0.192, **** P  < 0.0001) and myosin heavy chain (0.3901 ± 0.047 vs. 0.7222 ± 0.082, ** P  < 0.01) protein levels and reduction of muscle atrophy F‐box (10.77 ± 2.674 vs. 1.518 ± 0.172, ** P  < 0.01) expression. In dexamethasone‐induced muscle atrophy model, mice with genetic ablation of PDK4 revealed increased muscle strength (162.1 ± 22.75 vs. 200.1 ± 37.09 g, *** P  < 0.001) and muscle fibres (54.20 ± 11.85% vs. 84.07 ± 28.41%, **** P  < 0.0001). To explore the mechanism, we performed coimmunoprecipitation and liquid chromatography‐mass spectrometry analysis and found that myogenin is novel substrate of PDK4. PDK4 phosphorylates myogenin at S43/T57 amino acid residues, which facilitates the recruitment of muscle atrophy F‐box to myogenin and leads to its subsequent ubiquitination and degradation. Finally, overexpression of non‐phosphorylatable myogenin mutant using intramuscular injection prevented dexamethasone‐induced muscle atrophy and preserved muscle fibres. Conclusions: We have demonstrated that PDK4 mediates dexamethasone‐induced skeletal muscle atrophy. Mechanistically, PDK4 phosphorylates and degrades myogenin via recruitment of E3 ubiquitin ligase, muscle atrophy F‐box. Rescue of muscle regeneration by genetic ablation of PDK4 or overexpression of non‐phosphorylatable myogenin mutant indicates PDK4 as an amenable therapeutic target in muscle atrophy.